2013
DOI: 10.1155/2013/265980
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Bone Morphogenetic Protein on DOPA- or Dopamine-Treated Titanium Surfaces to Enhance Osseointegration

Abstract: Titanium was treated with 3,4-dihydroxy-L-phenylalanine (DOPA) or dopamine to immobilize bone morphogenetic protein-2 (BMP2), a biomolecule. DOPA and dopamine solutions turned into suspensions, and precipitates were produced at high pH. Both treatments produced a brown surface on titanium that was thicker at high pH than low pH. Dopamine produced a thicker layer than DOPA. The hydrophobicity of the surfaces increased after treatment with dopamine independent of pH. Furthermore, there were more amino groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…These results are similar to previously reported results for dopamine solutions. 32,33 It is likely that Michael addition or Schiff base reactions are prevalent in the high-pH dopamine solutions, as reported elsewhere. 15 Based on this, we concluded that D-rhG has properties similar to those of dopamine.…”
Section: Modified Gelatin Solutionsmentioning
confidence: 71%
See 2 more Smart Citations
“…These results are similar to previously reported results for dopamine solutions. 32,33 It is likely that Michael addition or Schiff base reactions are prevalent in the high-pH dopamine solutions, as reported elsewhere. 15 Based on this, we concluded that D-rhG has properties similar to those of dopamine.…”
Section: Modified Gelatin Solutionsmentioning
confidence: 71%
“…[21][22][23] These treatments not only provide organic layers, but also increase immobilization of biological molecules on the surfaces of various materials. [24][25][26][27][28][29][30][31][32][33] Various methods for dopamine conjugation have been investigated, including direct chemical coupling with polysaccharides. Hyaluronic acid, heparin, and β-cyclodextrin have been conjugated with dopamine or DOPA to increase the adhesiveness of the original polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BMP-2 itself is osteoinductive, its osteogenic potency was markedly enhanced after incorporation into biomimetic calcium phosphate coatings. Jeonghwa et al [36] attempted to immobilize BMPs on dopamine-treated Ti surfaces to enhance osseointegration, and thought the immobilized BMP-2 specifically interacted with myoblasts and induces osteogenic differentiation. Therefore, they proposed that their method was convenient for covalently immobilizing BMP2 while retaining its biological activity.…”
Section: Polypeptidementioning
confidence: 99%
“…[20][21][22] In addition, as another non-canonical amino acid, phosphonated serine has been applied to underwater adhesion. [23][24][25] Such phosphate groups have been found in the underwater adhesive proteins of the sandcastle worm and caddy silks, 16,17 which interact specifically with a titanium surface.…”
mentioning
confidence: 99%